WHEAT AS A SOURCE OF RAW MATERIAL IN PASTE FOODS PRODUCTION ON TERRITORY OF VOJVODINA AUTONOMOUS PROVINCE - Boris Kuzman; Drago Cvijanović; Jonel Subić (Ekonomika Poljoprivrede (1979), 2007)
Importance of this research is to realize real production of wheat as a basic element for paste foods production in last period and paste foods consumption in VAP. Such analysis helps us see market investiture and possibility of penetration in it. Market its self becomes more selectively and turbulent. However, there is no only present competition among the producers who produce the same products or give the same services, but also is present so-called generic competition among the products and services which satisfy the same needs of consumers. Such competition could be prevented by detailed analysis of the market and it enables absolute long-term business. In order to realize changes in consumption, certain occurrences were compared with earlier periods. Gathered data were presented by graphs and tables and processed with standard mathematics and statistical methods.